Primer registro del Saí Grande Oreomanes fraseri (Passeriformes: Coerebidae? Thraupidae?) en la Argentina - Mazar Barnett, Juan (1998)
We report the observation of a Giant Conebill Oreomanes fraseri, the fírst record of this species for Argentina, and the southem most so far. The single bird was seen on 26 September 1997 in the steep-sided quebrada of the rio Peña Negra, about 10 km west of Rodeo Pampa, Salta at ca. 3150 m. Based on colour pattern we assume it was an immature. We found the bird in a partially logged Polylepis (Rosaceae) woodland. This habitat is being generally c1eared all over its range, giving a strong cause of concern for the conservation of this near-threatened species, and several others that share this habitat.